2017
DOI: 10.3847/2041-8213/aa624c
|View full text |Cite
|
Sign up to set email alerts
|

Sheath-accumulating Propagation of Interplanetary Coronal Mass Ejection

Abstract: Fast interplanetary coronal mass ejections (ICMEs) are the drivers of strong space weather storms such as solar energetic particle events and geomagnetic storms. The connection between the space-weather-impacting solar wind disturbances associated with fast ICMEs at Earth and the characteristics of causative energetic CMEs observed near the Sun is a key question in the study of space weather storms, as well as in the development of practical space weather prediction. Such shock-driving fast ICMEs usually expan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
(90 reference statements)
0
34
0
Order By: Relevance
“…Based on their model and the CME propagation time of 24 h 45 min in the event, the lower limit of the CME kinetic energy is estimated to be 1.5 × 10 33 erg, assuming that the upstream solar wind is slow (350 km s −1 ) and dense (∼9 cm −3 ). For this circumstance, a CME energy of 1.5 × 10 33 erg suggests that the associated flare is of soft X-ray (SXR) class X10, according to the procedure of Takahashi & Shibata (2017). Alternatively, for a fast (500 km s −1 ) and rarified (1 cm −3 ) ambient solar wind, the lower limit of the CME kinetic energy is estimated to be 1.4 × 10 32 erg, which suggests that the SXR source flare was X1 class.…”
Section: Scaling the Solar Flare Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Based on their model and the CME propagation time of 24 h 45 min in the event, the lower limit of the CME kinetic energy is estimated to be 1.5 × 10 33 erg, assuming that the upstream solar wind is slow (350 km s −1 ) and dense (∼9 cm −3 ). For this circumstance, a CME energy of 1.5 × 10 33 erg suggests that the associated flare is of soft X-ray (SXR) class X10, according to the procedure of Takahashi & Shibata (2017). Alternatively, for a fast (500 km s −1 ) and rarified (1 cm −3 ) ambient solar wind, the lower limit of the CME kinetic energy is estimated to be 1.4 × 10 32 erg, which suggests that the SXR source flare was X1 class.…”
Section: Scaling the Solar Flare Sizementioning
confidence: 99%
“…CMEs in interplanetary space are known to be decelerated mainly due to dynamic drag force (Cargill et al 1996;Manchester et al 2004;Vršnak et al 2013, Takahashi & Shibata 2017. Takahashi & Shibata (2017) showed that the deceleration is caused by the accumulation of sheath plasmas ahead of the CMEs. They showed an analytic expression of CME Sun-Earth travel time in terms of its mass and speed near the Sun and validated their model with observations.…”
Section: Scaling the Solar Flare Sizementioning
confidence: 99%
“…It is known that extreme interplanetary coronal mass ejections (ICMEs) released from sunspots can cause severe magnetic storms, especially when they have southward magnetic fields (e.g., Tsurutani et al, 1992Tsurutani et al, , 2008Gonzalez et al, 1994;Daglis, 2000Daglis, , 2004Daglis and Akasofu, 2004;Willis & Stephenson, 2001;Willis et al, 2005;Echer et al, 2008b;Vaquero et al, 2008;Vaquero & Vazquez, 2009;Schrijver et al, 2012;Odenwald, 2015;Lakhina & Tsurutani, 2016;Hayakawa et al, 2017c;Usoskin, 2017;Takahashi and Shibata, 2017;Riley et al, 2018). During magnetic storms, the horizontal component of geomagnetic fields decreases at low and middle latitudes (Gonzalez and Tsurutani, 1987;Gonzalez et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Tappin () and Takahashi and Shibata () have used conservation of momentum to derive the expected thickness of a sheath, assuming that the momentum lost by a CME during transit goes into accelerating the solar wind material swept up in the sheath. Assuming the CME mass, MCME, remains constant, conservation of momentum gives the following relation between the mass in the sheath at time t, Msheathfalse(tfalse), the velocity of the CME at time zero, vCMEfalse(t0false), and the solar wind velocity vSW (assumed to be constant at the relevant distances).…”
Section: Theorymentioning
confidence: 99%
“…From here, we make our own simplifying assumptions to derive the standoff distance from equation . Similar to how Takahashi and Shibata () represent the sheath mass, we assume the CME mass can be expressed as the product of the volume and the CME density, ρCME, and that the CME volume depends on the solid angle of the CME, normalΩ, and its radial distance R. For the CME, we assume the thickness in the radial dimension is uniformly DCME over the full region given by normalΩ, yielding the following expression for the CME mass.…”
Section: Theorymentioning
confidence: 99%